2021
DOI: 10.3389/fgeed.2021.618378
|View full text |Cite
|
Sign up to set email alerts
|

Gene Editing of Hematopoietic Stem Cells: Hopes and Hurdles Toward Clinical Translation

Abstract: In the field of hematology, gene therapies based on integrating vectors have reached outstanding results for a number of human diseases. With the advent of novel programmable nucleases, such as CRISPR/Cas9, it has been possible to expand the applications of gene therapy beyond semi-random gene addition to site-specific modification of the genome, holding the promise for safer genetic manipulation. Here we review the state of the art of ex vivo gene editing with programmable nucleases in human hematopoietic ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 172 publications
(265 reference statements)
0
31
0
Order By: Relevance
“…The best-established strategies for HSPC gene therapy (HSPC-GT) are based on gene replacement by integrating vectors, such as lentiviral vectors (LVs), which semi-randomly introduce one or more functional copies of the affected gene in the genomic DNA of targeted cells (Naldini, 2019). The recently emerged gene-editing tools enable site-specific deletions, insertions, nucleotide substitutions, and the targeted integration of a therapeutic transgene, allowing to suppress or, conversely, rescue the function and physiological expression of the targeted gene and offering the promise of more precise, versatile, and safer genetic manipulation (Doudna, 2020;Ferrari et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…The best-established strategies for HSPC gene therapy (HSPC-GT) are based on gene replacement by integrating vectors, such as lentiviral vectors (LVs), which semi-randomly introduce one or more functional copies of the affected gene in the genomic DNA of targeted cells (Naldini, 2019). The recently emerged gene-editing tools enable site-specific deletions, insertions, nucleotide substitutions, and the targeted integration of a therapeutic transgene, allowing to suppress or, conversely, rescue the function and physiological expression of the targeted gene and offering the promise of more precise, versatile, and safer genetic manipulation (Doudna, 2020;Ferrari et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…They also suffer from insufficient sensitivity towards low-frequency off-target events ( 95 ) (. One strategy for making the most of these technologies is to combine biased and unbiased methods to generate a predicted list of OTE sites, then edit the cell type of interest and use NGS to confirm OTEs ( 96 ). Caution is advised in discarding predicted OTEs as NGS can only detect mutations present in at least 0.1-0.01% of cells.…”
Section: Outstanding Challenges In the Field Of Hsc Gene Editingmentioning
confidence: 99%
“…Indeed, it is well known that prolonged culture and stimulation of HSPCs, while being needed for efficient gene transfer, may adversely impact their engraftment and long-term repopulation capacity. Recent findings showed that addition to the culture medium of stemness preserving compounds, such as Stem Regenin-1, UM171, and 16,16-dimethyl prostaglandin E2 (dmPGE2), helps to maintain the long-term multilineage repopulation capacity of human corrected HSPCs transplanted in immunodeficient mouse models, partially overcoming the drawbacks of prolonged culture ( 96 ) and that fine-tuning of cytokine composition can lead to a beneficial balance between preservation of stemness and cell expansion ( 115 , 116 ). Another aspect that needs special attention is the tolerability of HSPCs to genetic modifications; indeed LT-HSCs, which require protection from mutational load over a lifetime, are more sensitive to DNA manipulation than differentiated cells, hence GE may trigger cellular responses that reduce their fitness and stemness.…”
Section: Outstanding Challenges In the Field Of Hsc Gene Editingmentioning
confidence: 99%
“…In the context of searching for new therapies, haematopoietic gene therapy has undergone unprecedented progress in terms of safety and efficacy [ 7 , 8 , 9 , 10 ]. The unique self-renewing and multi-potent properties of haematopoietic stem cells (HSCs), which can generate the entire haematopoietic lineage, make them ideal targets for gene correction of haematopoietic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The unique self-renewing and multi-potent properties of haematopoietic stem cells (HSCs), which can generate the entire haematopoietic lineage, make them ideal targets for gene correction of haematopoietic diseases. In addition, our considerable knowledge and experience about bone marrow autologous transplantation, which makes it possible to collect, genetically manipulate ex vivo and reinfuse the edited HSCs, would allow the evaluation and selection of correctly edited cells, improving the effectiveness of the process [ 9 ].…”
Section: Introductionmentioning
confidence: 99%